Influence of filler properties on the rheological, cryogenic, fatigue and rutting performance of mastics. (10th December 2019) - Rochlani, Mrinali; Leischner, Sabine; Falla, Gustavo Canon; Wang, Dawei; Caro, Silvia; Wellner, Frohmut
Highlights: We evaluated four mastics prepared with a single base bitumen and different fillers. The physical and chemical properties of the fillers were characterized. We assessed the linear viscoelastic and mechanical performance of the mastics. Several correlations between filler and mastic properties were identified. Performance diagrams are proposed to rank the overall quality of different mastics. Abstract: This paper compares the rheology properties and mechanical performance of four mastics fabricated with the same base bitumen and four different fillers (dolomite, granodiorite, limestone and rhyolite). The main objective of the investigation was to measure the impact that the filler exerts on the mechanical response of the bitumen. An experimental campaign using the dynamic shear rheometer was performed to quantify rheological properties of the different mastics under both, unaged and aged conditions, as well as their fatigue, rutting and low-temperature cracking susceptibility. A main finding is that the specific surface area of the filler was the most sensitive parameter affecting the mechanical response of the mastics. Also, it was observed that the mastic prepared with granodiorite filler showed the best fatigue and rutting resistance. The results of the investigation were synthesized through a 'performance diagram' that can be used for ranking and characterising bituminous mastics.